Chemical treatment of wheat straw on intake and nutrient utilization in sheep - SAHOO, B; SARASWAT, M L; HAQUE, N; KHAN, M Y (The Indian Journal of Animal Sciences, 2014)
Muzaffarnagari sheep randomly assigned to 3 groups of 5 animals each were used to study the effect of chemically treated wheat straw on nutrient utilization. Wheat straw was treated either with urea (4 kg urea/ 100 kg DM) with a storage time of 21 days (treatment 1 control) or urea supplementation (1.5 kg/ 100 kg DM) without storage time (treatment 2) or urea plus calcium hydroxide (3 kg urea plus 3 kg calcium hydroxide/100 kg DM ) with a storage time of 21 days (treatment 3). All the animals were allowed to fed respective diet ad lib. The crude protein (CP) content of wheat straw during feeding was 7.8%, 7.9% and 7.6% in treatments 1,2 and 3, respectively. Corresponding dry matter (DM) intake was 50.7.37.8 and 52,7 g/kg W0.75/day, respectively. which was higher (P